Personality. Development of Thought Throughout Time. Existence - A. E. Razumov (Moscow Polytechnic University, 2020)
Each personality contains a part of the fullness and depth of the World and the completeness of it depends on personality's own abilities and talents. Each «I» has the right to consider itself valuable and can claim to have a dialogue with another personality. A personality can evaluate and contain various cultures, knowledge and beliefs, science and religions. Each personality actualizes what can be called the development of thought throughout time. Moreover, not only «in the time» in sense of Newton's and Einstein's physics, but, mainly, in what we call «the time of the appearance of the Savior», «Shakespeare's time », «our time». That is, a set of conditions under which historical events occur. All these times are characterized by their own way of thinking and their own level of knowledge. And their own laws of existence. This means not only the factual existence, but also that exists in the imagination of the individual. At the same time, imaginary reality can more affect a person's worldview than actual reality. The development of thought throughout time brought a lot of useful things to a person, but also a lot of disastrous ones, such as conflicts and wars, global catastrophic risk, world-wide pre-crisis ecology problems, and a lot of other troubles - all these that can direct a person's thought towards dreams and imagination. Current problems of time, of course, disappear and are absorbed by Eternity. Eternity embraces and completes all time and existence. However, if you connect your imagination, then an inquisitive, free thought can assume the existence of the Pre-Eternal. Absolute, God. Just assume that He controls us, but we must trust Him with many of our concerns. Existence is a fundamental category. You can exist in reality or in imagination...or in the reality of imagination. The author considers the conversation about existence for himself not yet complete...